(untitled) (Scientific journal of the Fergana State University, 2023)
The article shows the emergence of the work "Padarkush" written by Mahmudkhoja Behbudi, a supporter of enlightenment and development, based on the first dramatic genre in the Turkestan region, and it is the basis for creating dozens of other modern jadid dramas. The work served as a major factor in the emergence and formation of modern Jadid dramaturgy. The purpose of the article is to bring to the reader the problem of this topic in modern dramas, following the idea of enlightenment raised in "Padarkush".